PENGARUH GOOD CORPORATE GOVERNANCE (GCG), CORPORATE SOCIAL RESPONSIBILITY (CSR), DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Consumer Non-Cyclicals Yang Terdaftar di BEI Pada Tahun 2018-2022) - Anisa, Anisah Lathifah; Nasution, Yuslinda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
The aim of this research is to find out and obtain empirical evidence about the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR) and Firm Size on Company Financial Performance in Manufacturing Companies in the Consumer Non Cyclical Sector listed on the Indonesia Stock Exchange for the 2018-2022 Period. The company characteristic factors used in this research include: Managerial Ownership, Institutional Ownership, Independent Board of Commissioners, Audit Committee, CSR, Firm Size and ROA. Measurement of corporate social responsibility is based on the Global Reporting Initiative (GRI) which is seen from the company's annual report. The sample in this study used a purposive sampling method to obtain 39 companies that met the criteria. Meanwhile, the data used in this research is secondary data obtained by accessing the official website www.idx.co.id. The results of this research simultaneously show that Good Corporate Governance (GCG), Corporate Social Responsibility (CSR) and Firm Size influence the Company's Financial Performance. Partially, Good Corporate Governance (GCG) has no effect on Company Performance, while Corporate Social Responsibility (CSR) has an effect on Company Performance and Company Size has no effect on Company Performance.